Structure evolution of tungsten coatings exposed to plasma flows under ITER ELM relevant conditions - Malykhin, S.V.; Surovitskiy, S.V.; Makhlaj, V.A.; Aksenov, N.N.; Byrka, O.V.; Borisova, S.S.; Herashchenko, S.S.; Reshetnyak, V.V. (Вопросы атомной науки и техники, 2017)
Structure, substructure and stress parameters both on the surface and distributed by depth in the tungsten/steel coatings exposed to high energy hydrogen plasma fluxes were studied by X-ray diffraction methods. The hydrogen plasma exposure results in the following recrystallization processes in the thin surface layer of the coating: appearing the texture axis [100] normal to the surface; increasing the coherence length from 60 nm in the initial state to 80 nm after the plasma exposure; completely annealed micro-strains; and dislocation density lowered twice in the exposed surface layer - all these facts confirm the thermal character of the hydrogen plasma influence. No structure variations were observed already at the depth near 1 m of the coating. Методами рентгеновской дифракции изучено изменение параметров структуры, субструктуры и напряжённого состояния на поверхности и по глубине покрытий вольфрам/сталь после облучения потоком водородной плазмы. Облучение плазмой приводит к рекристаллизационным процессам в тонком поверхностном слое покрытия: появлению текстуры [100] по нормали к поверхности, увеличению областей когерентного рассеяния от 60 нм в исходном состоянии до 80 нм после облучения, полному отжигу микронапряжений, а также уменьшению в два раза плотности дислокаций. Это подтверждает термический характер воздействия водородной плазмы. Уже на глубине около 1 мкм в покрытии никаких структурных изменений не выявлено. Методами рентгенівської дифракції вивчено змінення параметрів структури, субструктури та напруженого стану на поверхні та по глибині покриттів вольфрам/сталь після опромінення потоком водневої плазми. Опромінення плазмою призводить до рекристалізаційних процесів у тонкому поверхневому шарі покриття: виникненню текстури [100] по нормалі до поверхні, збільшенню областей когерентного розсіювання від 60 нм у початковому стані до 80 нм після опромінення, повному відпалу мікронапружень, а також зменшенню у двічі густини дислокацій. Це підтверджує термічний характер впливу водневої плазми. Вже на глибині біля 1 мкм у покритті ніяких структурних змін не виявлено.